The Belgian commitment to pharmaceutical quality: a model policy to improve quality assurance of medicines available through humanitarian and development programs - Raffaella Ravinetto; Tim Roosen; Catherine Dujardin (Taylor & Francis Group, 2018)
Today, a combination of globalization of pharmaceutical production, lack of regulatory harmonization, and weakness of Medicines Regulatory Authorities, creates the "perfect conditions" for poor-quality medicine to circulate in the global market and to penetrate the less-regulated countries. Medicines regulation is the responsibility of the national regulatory authorities in the recipient country, but in the poorer countries, in practice, the responsibility of supply of quality-assured medicines is often taken by Non-Governmental Organizations and other implementers. But with some notable exceptions, many donors lack a pharmaceutical procurement policy with adequate quality requirements; and many implementers lack the skills and expertise needed to orient themselves in the complex web of global pharmaceutical supply. Thus, patients served by humanitarian or development programs may remain exposed to the risk of poor-quality medicines. When public money is used to purchase medicines for medical programs to be carried out overseas, adequate policies should be in place to assure that the same quality requirements are set that would be required for medicines marketed in the "donor" country. We will describe here a policy recently adopted in Belgium, i.e. the "Commitment to Quality Assurance for Pharmaceutical Products", signed in October 2017 by the Vice Prime Minister and Minister for Development Cooperation and 19 Belgian implementing agencies. By signing the new policy, the counterparts committed to ensure quality of medicines in the programs funded by Belgium's Official Development Assistance, and to build quality-assurance capacity in the recipient countries. Implementers are requested to integrate in their financing applications a section for pharmaceutical quality assurance, with a justified budget. They are also invited to consider how costs could be rationalized and mutualized by aligning the strengths of the various implementers. This model policy has the potential to be considered for adoption by other donors, to help to reduce the current multiple standards in pharmaceutical quality, and to contribute to protect vulnerable communities from the plague of poor-quality medicines.